2013
DOI: 10.1002/jcb.24663
|View full text |Cite
|
Sign up to set email alerts
|

Dominant Negative MCP‐1 Blocks Human Osteoclast Differentiation

Abstract: Human osteoclasts were differentiated using receptor activator of NFκB ligand (RANKL) and macrophage colony stimulating factor (M-CSF) from colony forming unit-granulocyte macrophage (CFU-GM) precursors of the myeloid lineage grown from umbilical cord blood. Gene expression profiling using quantitative polymerase chain reaction (Q-PCR) showed more than 1,000-fold induction of chemokine MCP-1 within 24 h of RANKL treatment. MCP-1 mRNA content exceeds that of other assayed chemokines (CCL1, 3, 4, and 5) at all t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 39 publications
2
33
0
Order By: Relevance
“…Three cytokines were identified by the model as positive regulators of osteoclast and monocyte nuclei: IL-8, MCP-1 and VEGF. Of these cytokines, MCP-1 (Miyamoto et al, 2009; Morrison et al, 2014) and VEGF (Trebec-Reynolds et al, 2010; Zhang et al, 2008) were previously implicated as autocrine regulators of osteoclast formation and function consistent with model predictions. In contrast to previous reports demonstrating that TNFα plays a positive role as an autocrine regulator of osteoclast differentiation from mouse precursors (Nakao et al, 2007; Zou et al, 2001), we did not observe strong correlation of this factor with formation of human osteoclasts.…”
Section: Discussionsupporting
confidence: 69%
“…Three cytokines were identified by the model as positive regulators of osteoclast and monocyte nuclei: IL-8, MCP-1 and VEGF. Of these cytokines, MCP-1 (Miyamoto et al, 2009; Morrison et al, 2014) and VEGF (Trebec-Reynolds et al, 2010; Zhang et al, 2008) were previously implicated as autocrine regulators of osteoclast formation and function consistent with model predictions. In contrast to previous reports demonstrating that TNFα plays a positive role as an autocrine regulator of osteoclast differentiation from mouse precursors (Nakao et al, 2007; Zou et al, 2001), we did not observe strong correlation of this factor with formation of human osteoclasts.…”
Section: Discussionsupporting
confidence: 69%
“…Consistent with that phenotype, ITGBL1-overexpressing cancer cells showed elevated levels of RANKL and decreased expression of osteoprotegerin. Moreover, ITGBL1 positively regulated the secretion of the osteoclast differentiation activators GM-CSF (34), GRO (35), IL1a (36), MCPs (37), and MSP-a (38) in cancer cells, providing additional evidence supporting the role of ITGBL1 in cancer cell-triggered osteolytic lesions in bone metastatic events.…”
Section: Discussionmentioning
confidence: 82%
“…In addition, our previous study showed that 7ND protein prevents not only particle-induced macrophage chemotaxis, but also particle-induced inflammation in vitro [16]. Furthermore, 7ND has been shown to inhibit osteoclast differentiation of human colony forming unit-granulocyte macrophages (CFU-GM) in vitro [36]. Taken together 7ND coating reduced both the number of infiltrating macrophages and possibly the amount of particle-induced secretion of pro-inflammatory factors.…”
Section: Discussionmentioning
confidence: 99%